2018
DOI: 10.1039/c8qi00325d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Au-V2O5 composite nanowires through the shape transformation of a vanadium(iii) metal complex for high-performance solid-state supercapacitors

Abstract: Au-V2O5 composite nanowires with truncated octahedral morphology are synthesised through the shape transformation of a vanadium(iii) metal complex for use in high-performance solid-state supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Presumably, the dissolution of Fe 3 O 4 occurs due to its instability, and simultaneous growth of Fe 2 O 3 around the Au(0) nucleation center is favored under reaction conditions to form a morphologically pure Au–Fe 2 O 3 nanorod (Figure S7). Based on the experimental phenomena, it can be concluded that the dissolution–nucleation–recrystallization process suggested here is rational.…”
Section: Resultsmentioning
confidence: 76%
“…Presumably, the dissolution of Fe 3 O 4 occurs due to its instability, and simultaneous growth of Fe 2 O 3 around the Au(0) nucleation center is favored under reaction conditions to form a morphologically pure Au–Fe 2 O 3 nanorod (Figure S7). Based on the experimental phenomena, it can be concluded that the dissolution–nucleation–recrystallization process suggested here is rational.…”
Section: Resultsmentioning
confidence: 76%
“…In the same HRTEM image (Figure 2d), three separate fringe spacings at 0.23, 0.32, and 0.37 nm were obtained, which indicated respectively the presence of Au, 31 V 2 O 5 , 29 and MnO 2 . 29 Surface area analysis by the BET method indicated a higher specific surface area (65.5 m 2 g −1 ) of the composite compared to commercial V 2 O 5 (11 m 2 g −1 ) (Figure S2a). As per Brunauer classification, the synthesized Au−V 2 O 5 −MnO 2 nanocomposite and pristine V 2 O 5 resemble a type IV isotherm along with the adsorption hysteresis loops indicating the mesoporous structures of the nanomaterials.…”
Section: Electrochemical Studiesmentioning
confidence: 70%
“…29 At high py concentration, the morphological evolution of the VMC is truncated octahedral, whereas at low py concentration, it is octahedral in nature. 29 Because of the presence of more defects and faces, the truncated octahedral VMC is more reactive than the octahedral VMC. The preparation of a Au−V 2 O 5 −MnO 2 nanocomposite with flowerlike morphology is really challenging as well as interesting.…”
Section: Electrochemical Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…This material displayed a high energy density of 45.9 W h kg –1 at a power density of 700 W kg –1 and a remarkable cyclic ability with over 95% retention of capacitance after 9000 cycles. Furthermore, a sensible active material composition such as Co 3 O 4 –SnO@SnO 2 , Cu x O–V 2 O 5 /CNF, GF-CNT@Fe 2 O 3 , hollow carbon@MoS 2 /MoO 2 nanospheres, Au–V 2 O 5 nanowires, and VO 2 /Fe-PANI nanograins also offers a hopeful avenue for improving SC efficiency.…”
Section: Other Metal Oxides In a Supercapacitormentioning
confidence: 99%